Optimalisasi Teknologi Hidroponik Sebagai Upaya Meningkatkan Produktivitas dan Kualitas Tanaman Selada di Desa Prajegan Sukorejo Ponorogo - Aswin Hidayatulloh; Suci Midsyahri Azizah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Food security in Prajegan Village, Sukorejo Ponorogo, is still considered vulnerable. One of the efforts to overcome this is by applying hydroponic technology for lettuce cultivation. Lettuce cultivation with soil media in this village has several disadvantages, such as slow growth, low yields, suboptimal quality, susceptibility to pests and diseases, and large land requirements. Hydroponics, a soil-less method of plant cultivation, offers a solution through faster growth, higher yields, optimised quality, resistance to pests and diseases, and land saving. This study aims to analyse the effect of hydroponics on the productivity and quality of lettuce plants in Prajegan Village, Sukorejo Ponorogo. This type of research method used is a type of field research, namely research carried out by going directly to the place of the object of research, in order to obtain the data needed, especially data specific to the research The results showed that hydroponics significantly increased the productivity and quality of lettuce plants. Hydroponic lettuce grows faster, produces higher yields, and has more optimal quality compared to lettuce grown with soil media. This shows that hydroponics can be an effective solution to improve food security in Prajegan Village, Sukorejo Ponorogo.